Facilitating subtiligase-catalyzed peptide pigation reactions by using peptide thioester substrates - Tan, Xiaohong (2020)
By facilitating formation of the acyl–enzyme intermediate, peptide thioesters can largely promote subtiligase-catalyzed ligation reactions over their ester counterparts. This offers a significant addition to the repertoire of enzymatic methods for protein chemical synthesis and modification.